High Aluminum Tolerance of Rhodotorula sp. RS1 is Associated with Thickening of the Cell Wall Rather than Chelation of Aluminum Ions - WANG, Chao; ZHAO, Xue-Qiang; AIZAWA, T.; SUNAIRI, M.; SHEN, Ren-Fang (Pedosphere, 2013)
Aluminum （Al） is very toxic to many living organisms, including plants, animals and microorganisms. However, despite many studies on Al tolerance in plants, little has been reported concerning these mechanisms in microorganisms. In this study, a red yeast, which could tolerate Al3＋ concentrations as high as 200 mmol L-1, was isolated from acidic soils, identified as Rhodotorula sp. and designated as RS1. As the medium compositions can greatly affect the responses of microorganisms to Al, two culture mediums, glucose medium （GM） and lysogeny broth medium containing soil extract （S-LBM）, were used. During growth of RS1, the pH of medium decreased in GM but increased in S-LBM. These changes in the pH of the media were not induced by Al addition. No or little secretion of organic acids was observed in RS1 growth media. Importantly, the thickness of the cell walls and the ratio of cell wall to biomass of RS1 significantly increased in GM with high Al3＋ concentrations. In the presence of 100 mmol Al L-1, 78.0% of the total A1 of whole cells was present in the thickened cell walls. The Al in cell walls was mostly bound to OH, amide and CO groups of polysaccharides. These results suggest that thickening of the cell wall in response to the high Al3＋ concentrations may play an important role in the high tolerance of RS1 to Al and that pH increase of the medium and chelation of Al ions are not involved in Al tolerance of this organism.